Survey Evaluation of an Approach for Dynamic Software Product Lines - Guedes, Gabriela; Silva, Carla; Soares, Monique (Cadernos do IME - Série Informática, 2021)
In Dynamic Software Product Lines (DSPLs) product configuration occurs at runtime. Modelling variability and configuring the product in DSPLs should consider the context and non-functional requirements (NFRs) satisfaction. ConG4DaS (Contextual Goal models For Dynamic Software product lines) is a Requirements Engineering (RE) approach for DSPL which supports (i) modelling of variability with goals, NFRs, contexts and the relationship be-tween them; and (ii) offers a product configuration based on contexts, NFRs and their priority and interactions. In this paper, we present a survey evaluation of ConG4DaS with RE and DSPL researchers in regard to the perceived usefulness. In the survey, both RE and DSPL researchers perceived ConG4DaS as useful for modelling and configuring DSPLs. However, the RE group gave more positive answers than the DSPL group.